Gonopterodendron sarmientoi Lorentz ex Griseb (palo santo): evaluation of growth for timber purposes - Chifarelli, Vanina; Senilliani,, María Gracia; Longhi-Santos, Tomaz; Moglia, Juana Graciela; Gimenez, Ana María (Instituto de Ecología, A.C., 2022)
Gonopterodendron sarmientoi Lorentz ex Griseb AC Godoy-Bürki (Zigophyllaceae) is an endemic species of northwestern Argentina, included in Appendix II of the International Convention on Trafficking in Endangered Species of Wild Fauna and Flora. This research seeks to determine the cutting cycle based on the age of Gonopterodendron sarmientoi, estimated from the measurement of the growth rings, applying a diameter growth equation according to the site. We worked in 4 sites according to the climatic gradient of precipitation, selecting 35 trees given their limitations and restrictions regarding their extraction contemplated by law 22 344 (Convention on International Trade in Endangered Species of Wild Fauna and Flora). The general equation and the one obtained by sites (Las Lomitas, Ingeniero G. Juárez, Las Hacheras, and Rivadavia), were adjusted by regression with linear mixed models. The average thickness obtained was 3.03 mm with an average rotation of 41 years and a transit time of 12 years. Las Lomitas is the site with the highest annual increase with an average thickness of 3.4 mm and the highest harvest age of 81 years; Las Hacheras had an average thickness of 3.08 mm and the lowest harvest age at 41 years; Rivadavia recorded a thickness of 2.68 mm and a harvest age of 59 years; and Ingeniero G. Juárez presented a thickness of 2.19 mm with a harvest age of 52 years. The results of this work reliably determined the cutting shifts and rotation times that will contribute to the sustainable forest management of the species.